A portable single‐sided magnet system for remote NMR measurements of pulmonary function. (23rd June 2014) - Dabaghyan, Mikayel; Muradyan, Iga; Hrovat, Alan; Butler, James; Frederick, Eric; Zhou, Feng; Kyriazis, Angelos; Hardin, Charles; Patz, Samuel; Hrovat, Mirko; Rizi, Rahim R.
<x xml:space="preserve">Abstract</x> In this work, we report initial results from a light‐weight, low field magnetic resonance device designed to make relative pulmonary density measurements at the bedside. The development of this device necessarily involves special considerations for the magnet, RF and data acquisition schemes as well as a careful analysis of what is needed to provide useful information in the ICU. A homogeneous field region is created remotely from the surface of the magnet such that when the magnet is placed against the chest, an NMR signal is measured from a small volume in the lung. In order to achieve portability, one must trade off field strength and therefore spatial resolution. We report initial measurements from a ping‐pong ball size region in the lung as a function of lung volume. As expected, we measured decreased signal at larger lung volumes since lung density decreases with increasing lung volume. Using a CPMG sequence with ΔTE=3.5 ms and a 20 echo train, a signal to noise ratio 1100 was obtained from an 8.8mT planar magnet after signal averaging for 43 s. This is the first demonstration of NMR measurements made on a human lung with a light‐weight planar NMR device. We argue that very low spatial resolution measurements of different lobar lung regions will provide useful diagnostic information for clinicians treating Acute Respiratory Distress Syndrome as clinicians want to avoid ventilator pressures that cause either lung over distension (too much pressure) or lung collapse (too little pressure). Copyright © 2014 John Wiley & Sons, Ltd.